2021
DOI: 10.5152/tao.2020.5714
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Carvacrol against Paclitaxel-Induced Ototoxicity in Rat Model

Abstract: Objective: This study aimed to explore whether carvacrol (CV) had a protective effect on paclitaxel-induced ototoxicity from biochemical, functional, and histopathological perspectives.Methods: Forty Wistar albino male rats were randomly separated into five groups of eight rats. Group 1 was the control group, so Paclitaxel or CV was not administered. Group 2 was administered i.p. CV at 25 mg/kg once a week; Group 3, was administered i.p. paclitaxel at 5 mg/kg once a week; Group 4 was administered i.p. paclitax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 26 publications
3
19
0
Order By: Relevance
“…DPOAE measurement were performed 15 under anesthesia (ketamine -40 mg/kg + xylazine -5 mg/kg) before drug administration on day 0. Afterward, animals with no auditory pathological findings and whose baseline hearing threshold was evaluated were randomly divided into three groups.…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…DPOAE measurement were performed 15 under anesthesia (ketamine -40 mg/kg + xylazine -5 mg/kg) before drug administration on day 0. Afterward, animals with no auditory pathological findings and whose baseline hearing threshold was evaluated were randomly divided into three groups.…”
Section: Experimental Designmentioning
confidence: 99%
“…The sensitivity of neurons to PCX toxicity has guided clinical studies of the ototoxic effect of PCX on peripheral auditory neurons 12 13 . Recent studies on animal models have reported that substances such as curcumin, carvacrol, resveratrol, gallic acid, and eugenol, all of which have potent antioxidant properties, can attenuate chemotherapeutic drugs induced ototoxicity such as cisplatin and PCX [14][15][16][17][18] . Ototoxicity is accompanied by free radicals, resulting in oxidative damage to cochlear cells, which is why antioxidants are used in much research on preventing and restoring ototoxicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional chemotherapy, such as anthracyclines, taxols, cisplatin or other platinum-containing drugs, targets either DNA replication or repair, or interferes with tubulins, disabling proper chromatid exchange in mitosis. Oxidative stress commonly accompanies these therapies, which damage cancer cells, but also normal cells, thereby causing side effects such as cardiotoxicity or ototoxicity [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The O. vulgare ssp. hirtum essential oils are known to have pronounced antioxidant [13,57,64,65], protective action [66], as well as antimicrobial, antibacterial, antifungal properties and the ability to inhibit bacterial growth [15,18,54,64,65]. Due to these important characteristics, this essential oil is used as a preservative in food [27,67].…”
Section: Discussionmentioning
confidence: 99%